Dagboken fra Belgica-ekspedisjonen 1897-99 : Roald Amundsens første ferd til Antarktis - Amundsen, Roald (Vågemot miniforl., 1998)
Keywords: Antarktis; Belgica (skip); Roald Amundsen; dagbøker; oppdagelsesreiser; overvintring; polarekspedisjoner; vitenskap

Ice sheet history from Antarctic Continental Margin sediments: The ANTOSTRAT approach - Barker, Peter; Barrett, Peter; Camerlenghi, Angelo; Cooper, Alan; Davey, Frederick; Domack, Eugene; Escutia, Carlota; Kristoffersen, Yngve; O'Brien, Philip (Terra Antarctica, 1998)
Keywords: Antarktis; glasiologi; innlandsis; sedimentologi

“Convergence or National Styles? The Japanese Challenge to the British-Norwegian Hegemony in the Twentieth-Century Whaling Industry” - Basberg, Bjørn L (Global Markets: The Internationalization of the Sea Transport Industries since 1850, 1998)
Keywords: Antarktis; Svend Foyn; fiskeindustri; hvalfangst; hvalfangstindustri; hvalfangstnæring; hvalindustri; pelagisk; økonomi

Roald Amundsen : en biografi - Bomann-Larsen, Tor (Cappelen, 1998)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolen; biografi; ekspedisjoner; oppdagelsesreiser

On the cost of reproduction in long-lived birds: the influence of environmental variability - Erikstad, Kjell Einar; Fauchald, Per; Tveraa, Torkild; Steen, Harald (Ecology, 1998)
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norge og polarområdene - Hansson, Rasmus (ed.) (Utenriksdepartementet, 1998)
Keywords: Antarktis; Norge; geografi; historie; miljøvern; polarforskning; polarområdene; politikk

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

Antarctic Protected Areas Workshop : workshop report - Njåstad, Birgit (ed.) (Norsk Polarinstitutt, 1998)
Keywords: Antarktis; kongress; miljøvern; naturvern

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

A new species of Parmelia (lichenized Ascomycotina) from the Antarctic - Øvstedal, Dag Olav; Elix, John A.; Smith, Ronald I. Lewis (Mycotaxon, 1998)
A new species of Parmelia (lichenized Ascomycotina) from the Antarctic. Parmelia lindsayana Ovstedal & Elix from Signy Island (South Orkney Islands) is described as new. This species resembles P. protosulcata Hale and P. cunninghamii Crombie, but differs in morphological details and in containing usnic, alpha-collatolic and alectoronic acids.
Keywords: Antarktis; Sør-Orknøyene; botanikk; lav; planter

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

Sydpolen - Skattum, Ole Jacob (Roald Amundsen som geografisk oppdager, 1998)
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; oppdagelsesreiser

Caloplaca Lewis-Smithii, a new lichen species from continental Antarctica - Søchting, Ulrik; Øvstedal, Dag Olav (Mycotaxon, 1998)
A new muscicolous lichen species, Caloplaca lewis-smithii Søchting & Øvst., is described from Victoria Land, continental Antarctica. It is characterized by a grey to blackish brown microlobate thallus and a blackish apothecial disk with a white pruinose thalline margin.
Keywords: Antarktis; botanikk; lav; planter; sopper

The semi-annual oscillation and Antarctic climate. Part 1: influence on near surface temperatures (1957–79) - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
We studied the influence of the semi-annual oscillation (SAO) on near-surface temperatures in Antarctica, using observations of 27 stations that were operational during (part of) the period 1957–79. For the annual cycle of surface pressure, the second harmonic explains 17–36% of the total variance on the Antarctic Plateau, 36–68% along the East Antarctic coast and almost 80% on the west coast of the Peninsula, and decreases further to the north. As a result of the amplification of the wave-3 structure of the circulation around Antarctica, a significant modification of the seasonal cooling is observed at many stations. The magnitude of this modification is largely determined by the strength of the temperature inversion at the surface: the percentage of the variance explained by the second harmonic of the annual temperature cycle is then largest on the Antarctic Plateau (11–18%), followed by the large ice shelves and coastal East Antarctica (6–12%) and stations at or close to the Peninsula (0–5%). A significant coupling between the half-yearly wave in surface pressure and that in surface temperature is found for coastal East Antarctica, which can be directly explained by the changes in meridional circulation brought about by the SAO. We show that the coupling of Antarctic temperatures to the meridional circulation is not only valid on the seasonal time scale of the SAO, but probably also on daily and interannual time scales. This has important implications for the interpretation of time series of Antarctic temperatures, a problem that will be addressed in part 2 of this paper.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

The semi-annual oscillation and Antarctic climate. Part 2: recent changes - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
Following a weakening of the semi-annual oscillation (SAO) since the mid-1970s, the half-yearly pressure wave in the Southern Hemisphere has become less significant. As a result, May/June temperatures have decreased in East Antarctica, which has moderated Antarctic warming. Spectral analysis of 87 years of pressure data at Orcadas suggest that the recent weakening of the SAO is part of the natural variability of the Southern Hemisphere circulation on decadal timescales. We interpret the time series of composite Antarctic temperature in terms of the historical strengthening and weakening of the SAO. If the dominant oscillations that occurred in the past prove to be persistent, an accelerated East Antarctic warming trend is expected for the coming decades. There are indications that the strength of the SAO is linked to the Southern Oscillation, in the sense that warm phases of the Southern Oscillation coincide with strong westerlies, a weakly developed SAO and below-average temperatures in East Antarctica. Temperatures on the west coast of the Antarctic Peninsula show strongly deviant patterns, which can not be explained by the same mechanism that applies to East Antarctica.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

Validation of Ground-Based Visible Measurements of Total Ozone by Comparison with Dobson and Brewer Spectrophotometers - Van Roozendael, Michel; Peeters, P.; Roscoe, H. K.; De Backer, H.; Jones, A. E.; Bartlett, L.; Vaughan, G.; Goutail, Florence; Pommereau, Jean-Pierre; Kyro, E.; Wahlstrom, C.; Braathen, Geir; et al. (Journal of Atmospheric Chemistry, 1998)
Comparisons of total column ozone measurements from Dobson, Brewer and SAOZ instruments are presented for the period 1990 to 1995 at seven stations covering the mid- and the high northern latitudes, as well as the Antarctic region. The main purpose of these comparisons is to assess, by reference to the well established Dobson network, the accuracy of the zenith-sky visible spectroscopy for the measurement of total ozone. The strengths and present limitations of this latter technique are investigated. As a general result, the different instruments are found to agree within a few percent at all stations, the best agreement being obtained at mid-latitudes. On average, for the mid-latitudes, SAOZ O3 measurements are approximately 2% higher than Dobson ones, with a scatter of about 5%. At higher latitudes, both scatter and systematic deviation tend to increase. In all cases, the relative differences between SAOZ and Dobson or Brewer column ozone are characterised by a significant seasonal signal, the amplitude of which increases from about 2.5% at mid-latitude to a maximum of 7.5% at Faraday, Antarctica. Although it introduces a significant contribution to the seasonality at high latitude, the temperature sensitivity of the O3 absorption coefficients of the Dobson and Brewer instruments is shown to be too small to account for the observed SAOZ/Dobson differences. Except for Faraday, these differences can however be largely reduced if SAOZ AMFs are calculated with realistic climatological profiles of ozone, pressure and temperature. Other sources of uncertainties that might affect the comparison are investigated. Evidence is found that the differences in the air masses sampled by the SAOZ and the other instruments contribute significantly to the scatter, and the impact of the tropospheric clouds on SAOZ measurements is displayed.
Keywords: Antarktis; klimatologi; ozon; polarområdene; spektrofotometri; stratosfæren